2010
DOI: 10.1590/s0100-29452010005000131
|View full text |Cite
|
Sign up to set email alerts
|

Alteração da eficiência do 1-MCP com o retardo na sua aplicação após a colheita em maçãs 'Fuji suprema'

Abstract: Estudos indicam que a eficiência do 1-metilciclopropeno (1-MCP) para conservação pós-colheita de maçãs é máxima quando aplicado até uma semana após a colheita. No entanto, o carregamento das câmaras de armazenagem comerciais com maçãs 'Fuji' pode extender-se por mais de uma semana. Os efeitos da aplicação tardia do 1-MCP para maçãs 'Fuji' não têm sido reportados. Este trabalho teve por objetivo avaliar os efeitos do retardo na aplicação de 1-MCP, a partir da data de colheita, na preservação da firmeza de polpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Other studies have shown that delays in 1‐MCP application may or may not influence efficacy of the treatment. For example, Amarante et al showed that a delay of up to 20 days before application of 1‐MCP did not have a significant influence on the firmness of ‘Fuji’ apples after 9 months storage in air. However, their assessment was limited to the firmness at the end of storage, and after 7 days at 23 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that delays in 1‐MCP application may or may not influence efficacy of the treatment. For example, Amarante et al showed that a delay of up to 20 days before application of 1‐MCP did not have a significant influence on the firmness of ‘Fuji’ apples after 9 months storage in air. However, their assessment was limited to the firmness at the end of storage, and after 7 days at 23 °C.…”
Section: Resultsmentioning
confidence: 99%
“…52 Other studies have shown that delays in 1-MCP application may or may not influence efficacy of the treatment. For example, Amarante et al 53 showed that a delay of up to 20 days before application of 1-MCP did not have a significant influence on the firmness of 'Fuji' apples after 9 months storage in air. However, their assessment was limited to the firmness at the end of storage, and after 7 days at 23 ∘ C. In contrast, Watkins and Nock 13 showed that delaying CA application by 2 weeks resulted in a significant increase in the IECs, and significantly wileyonlinelibrary.com/jsfa The model parameter values were estimated by refitting the data to the model to obtain treatment-specific values for one of these three parameters, and keeping the other model parameters common for all treatments.…”
Section: Ethylene Production and Quality Evolutionmentioning
confidence: 99%
“…The storage duration was up to eight and ten months in years 2013 and 2014, respectively. 1-MCP application (1.0 μL L -1 ) was carried out in hermetic chamber of 1.0 m³ for 24 hours, according to methodology described by Amarante et al (2010).…”
Section: Methodsmentioning
confidence: 99%
“…According to Amarante et al (2010), the presence of ethylene in the storage environment stimulates α-farnesene formation, and O 2 favors its oxidation to trienes conjugates and 6-methyl-5-hepten-2-one (MHO-ona), responsible for the appearance of superficial scald on the fruit epidermis. Figure 1 -Ethylene production rate, respiration rate and background color of 'SCS426 Venice' apples submitted or not to 1-MCP application and stored in air atmosphere (AA) or controlled atmosphere (CA) for different periods.…”
Section: Days Of Storagementioning
confidence: 99%
See 1 more Smart Citation